Pearl Millet Aquaporin Gene PgPIP2;6 Improves Abiotic Stress Tolerance in Transgenic Tobacco - Reddy, Palakolanu Sudhakar; Dhaware, Mahamaya G.; Sivasakthi, Kaliamoorthy; Divya, Kummari; Nagaraju, Marka; Sri Cindhuri, Katamreddy; Kavi Kishor, Polavarapu Bilhan; Bhatnagar-Mathur, Pooja; Vadez, Vincent; Sharma, Kiran K. (Frontiers in Plant Science, 2022)
Pearl millet [Pennisetum glaucum (L) R. Br.] is an important cereal crop of the semi-arid tropics which can withstand prolonged drought and heat stress. Considering an active involvement of the aquaporin (AQP) genes in water transport and desiccation tolerance besides several basic functions, their potential role in abiotic stress tolerance was systematically characterized and functionally validated. A total of 34 AQP genes from P. glaucum were identified and categorized into four subfamilies, viz., PIPs, TIPs, NIPs and SIPs. Sequence analysis revealed that PgAQPs have conserved characters of AQP genes with a closer relationship to sorghum. The PgAQPs were expressed differentially under high progressive vapor pressure deficit (VPD) and progressive drought stresses where the PgPIP2;6 gene showed significant expression under high VPD and drought stress. Transgenic tobacco plants were developed by heterologous expression of PgPIP2;6 gene and functionally characterized under different abiotic stresses to further unravel their role. Transgenic tobacco plants in the T2 generations displayed restricted transpiration and low root exudation rates in low and high VPD conditions. Under progressive drought stress, wild-type (WT) plants showed a quick or faster decline of soil moisture than transgenics. While under heat stress, PgPIP2;6 transgenics showed better adaptation to heat (40 °C) with high canopy temperature depression (CTD) and low transpiration, under low-temperature stress, they displayed lower transpiration than their non-transgenic counterparts. Cumulatively, lower transpiration rate (Tr), low root exudation rate, declined transpiration, elevated CTD, and limited transpiration indicates that PgPIP2;6 plays a role under abiotic stress tolerance. Since the PgPIP2;6 transgenic plants exhibited better adaptation against major abiotic stresses such as drought, high VPD, heat, and cold stresses by virtue of enhanced transpiration efficiency, it has the potential to engineer abiotic stress tolerance for sustained growth and productivity of crops.